Mechanism of the allelopathic effect of macroalgae Gracilaria bailiniae on Nitzschia closterium - Bowen Huang; Jianjun Cui; Xinyi Chen; Yongjian Huang; Cong Xu; Enyi Xie (Ecotoxicology and Environmental Safety, 2022)
With the rapid development of the seaweed industry in China, the scale and production of its commercial seaweed are ranked among the most significant worldwide. Consequently, the control of algal blooms, especially fouling diatoms, during macroalgae industrialisation is an important issue. Many diatom bloom studies have focused on physical and chemical controls, with limited economic and eco-friendly biological controls reported. In our study, Gracilaria bailiniae fresh thalli and aqueous extract profoundly suppressed Nitzschia closterium growth (50% inhibition concentration of the fourth day (IC50–4 day) was 0.667 × 10−3 g·mL−1 and 3.889 × 10−3 g·mL−1, respectively). The cellular morphology changes of N. closterium exposed to the G. bailiniae aqueous extract were severe atrophies and plasmolysis and dissolution of endocellular structures. To explore more potential allelochemicals to control N. closterium, the intracellular compounds of G. bailiniae were detected and screened. Three organic acids (citrate, hydroxyethanesulfonic acid (HA) and taurine) had allelopathic potential against N. closterium. Our results showed that citrate and HA markedly suppressed N. closterium (IC50–4 day: 1.035 mM and 1.151 mM, respectively); however, taurine poorly suppressed N. closterium (IC50–4 day: 2.500 mM). Therefore, HA is one of the main allelopathic compounds in G. bailiniae. Further, the allelopathic mechanism of HA against the N. closterium photosynthetic system broke its photosynthetic apparatus (oxygen-evolving complex, reaction centres, the effective antenna size and the donor side of photosystem II) and hindered electron transport. The experimental results provide a new and eco-friendly strategy to control diatom blooms.